Ageing in Pgc-1β(−/−) mice modelling mitochondrial dysfunction induces differential expression of a range of genes regulating ventricular electrophysiology - Edling, Charlotte E. (Biosci Rep, 2019)
Mice deficient in mitochondrial promoter peroxisome proliferator activated receptor-γ co-activator-1β (Pgc-1β(−/−)) is a valuable model for metabolic diseases and has been found to present with several pathologies including ventricular arrhythmia. In the present study, our aim was to shed light on the molecular mechanisms behind the observed arrhythmic substrate by studying how the expression of selected genes critical for cardiac function differs in wild-type (WT) compared with Pgc-1β knockout mice and young compared with aged mice. We found that a clear majority of genes are down-regulated in the Pgc-1β(−/−) ventricular tissue compared with the WT. Although most individual genes are not significantly differentially expressed, a pattern is apparent when the genes are grouped according to their functional properties. Genes encoding proteins relating to ATPase activity, potassium ion channels relating to repolarisation and resting membrane potential, and genes encoding proteins in the cAMP pathway are found to be significantly down-regulated in the Pgc-1β deficient mice. On the contrary, the pacemaker channel genes Hcn3 and Hcn4 are up-regulated in subsets of the Pgc-1β deficient tissue. Furthermore, we found that with age, especially in the Pgc-1β(−/−) genotype, most genes are up-regulated including genes relating to the resting membrane potential, calcium homeostasis, the cAMP pathway, and most of the tested adrenoceptors. In conclusion, we here demonstrate how a complex pattern of many modest changes at gene level may explain major functional differences of the action potential related to ageing and mitochondrial dysfunction.